2010
DOI: 10.1371/journal.pone.0008909
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C Gamma 2 Is Critical for Development of a Murine Model of Inflammatory Arthritis by Affecting Actin Dynamics in Dendritic Cells

Abstract: BackgroundDendritic cells (DCs) are highly specialized cells, which capture antigen in peripheral tissues and migrate to lymph nodes, where they dynamically interact with and activate T cells. Both migration and formation of DC-T cell contacts depend on cytoskeleton plasticity. However, the molecular bases governing these events have not been completely defined.Methodology/Principal FindingsUtilizing a T cell-dependent model of arthritis, we find that PLCγ2−/− mice are protected from local inflammation and bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
(84 reference statements)
1
31
0
Order By: Relevance
“…In vivo immune phenotypes caused by genetic alterations of Plc␥2 have been described. We and others (12)(13)(14) have shown that PLC␥2 regulates inflammation and autoimmunity, specifically within the bone microenvironment. Plc␥2 Ϫ/Ϫ mice are protected from immune activation in serum transfer arthritis and antigen-induced arthritis (13,14).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In vivo immune phenotypes caused by genetic alterations of Plc␥2 have been described. We and others (12)(13)(14) have shown that PLC␥2 regulates inflammation and autoimmunity, specifically within the bone microenvironment. Plc␥2 Ϫ/Ϫ mice are protected from immune activation in serum transfer arthritis and antigen-induced arthritis (13,14).…”
Section: Discussionmentioning
confidence: 91%
“…We and others (12)(13)(14) have shown that PLC␥2 regulates inflammation and autoimmunity, specifically within the bone microenvironment. Plc␥2 Ϫ/Ϫ mice are protected from immune activation in serum transfer arthritis and antigen-induced arthritis (13,14). In humans, a dominantly inherited disease called PLAID (PLC␥2-associated antibody deficiency and immune dysregulation) is caused by mutant alleles of PLC␥2 in which small, in-frame genomic deletions eliminate part or all of the C-terminal SH2 domain of PLC␥2.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We have reported that ablation of PLCγ2 results in a blockade of osteoclastogenesis owing to defective NFATc1 induction (11,22). PLCγ2-deficient mice are osteopetrotic and are also protected from inflammatory osteolysis (23,24). Therefore, we sought to identify novel PLCγ2-dependent signaling mediators that could inform therapeutic design for disorders caused by OC overactivity, such as osteoporosis and RA.…”
Section: Resultsmentioning
confidence: 99%